'But I doubt not the people': beasts of the apocalypse in Thomas Müntzer and King Lear. Issue 12 (2nd December 2021) - Gilchrist Hall, Sam
ABSTRACT: Shakespeare and Müntzer place an extraordinary belief in ordinary people. In the preacher's uniquely histrionic understanding of the eucharist, it is the congregation that enable its mysterious transformations, while Shakespeare insists that the 'rough magic' ( The Tempest, 5.1.50) of the stage happens because of his audience. Both suggest that common folk have a responsibility to speak their minds and act according to their consciences. Although many of the themes, tropes and images their works share were drawn quite separately from the Bible's prophetic books and their native apocalyptical traditions, this article illustrates the comparable ways in which inbrutation is used to attack the hypocrisies and downright malice of the powers that be. However, whereas Müntzer remained convinced that tribulations of this vale of tears would be overcome at Doomsday, Shakespeare's conception of 'the promis'd end' ( Lear, 5.2.238) is essentially tragic, for the agonies he stages are in no way redeemed. Indeed, Lear implies that the desire to return to Eden, which motivated Müntzer and his compatriots to take up arms against the princes of the Holy Roman Empire, is dangerously reactionary.